2007
DOI: 10.1080/00926230601098449
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy, Orgasm Likelihood, and Conflict Predict Sexual Satisfaction in Heterosexual Male and Female Respondents

Abstract: Anonymous data provided by 417 female and 179 male sexually active heterosexual respondents showed that in long term sexual relationships, sexual satisfaction was positively correlated with two different intimacy variables, the respondent's orgasm likelihood, and negatively correlated with conflict in the relationship. Multiple linear regression permitted us to measure the effect sizes of these variables as predictors of sexual satisfaction. These findings have important implications for treatment of symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 30 publications
(22 reference statements)
3
65
0
5
Order By: Relevance
“…Interestingly, moderate to strong correlations reported in this study were similar in magnitude to the associations between emotional intimacy and sexual satisfaction previously reported in studies conducted among heterosexual individuals and couples (Hanning et al, 2007;Sprecher, 2002). In contrast to the once widespread belief that gay men are incapable of developing relationship intimacy (Frost, 2011;Meyer & Dean, 1998) and that male same-sex couples are emotionally disengaged (Balsam et al, 2008), our findings strongly suggest that the role of intimacy in men's romantic relationships and sexual satisfaction is not sexual orientation-specific.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, moderate to strong correlations reported in this study were similar in magnitude to the associations between emotional intimacy and sexual satisfaction previously reported in studies conducted among heterosexual individuals and couples (Hanning et al, 2007;Sprecher, 2002). In contrast to the once widespread belief that gay men are incapable of developing relationship intimacy (Frost, 2011;Meyer & Dean, 1998) and that male same-sex couples are emotionally disengaged (Balsam et al, 2008), our findings strongly suggest that the role of intimacy in men's romantic relationships and sexual satisfaction is not sexual orientation-specific.…”
Section: Discussionsupporting
confidence: 89%
“…It is, therefore, not surprising that empirical research showed the association between intimacy and multiple beneficial personal and relationship outcomes, including psychological well-being (Frost, 2013;Frost & Forrester, 2013), physical health (Pietromonaco, Uchino, & Schetter, 2013;Stadler, Snyder, Horn, Shrout, & Bolger, 2012), and a greater marital and relationship satisfaction (Greeff & Malherbe, 2001;Hassebrauck & Fehr, 2002;Patrick, Sells, Giordano, & Tollerud, 2007). Several studies have also shown that intimacy has a significant, pleasure-enhancing role in one's sex life (Hanning et al, 2007;Moret, Glaser, Page, & Bargeron, 1998;Sprecher, 2002;Štulhofer, Ferreira, & Landripet, 2014).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…22 Voor zowel mannen als vrouwen geldt dat mensen die aangeven bijna altijd of altijd een orgasme te bereiken, vaker rapporteerden eerder tevreden of heel tevreden te zijn over hun seksleven. Dit laatste verband vormt een bevestiging van eerdere studies (Haning et al, 2007). In onze bevraging heeft 72% van de mannen (77% van diegenen die ooit hebben gemasturbeerd) en 48% van de vrouwen (68% van diegenen die ooit hebben gemasturbeerd) de afgelopen zes maanden minstens één keer gemasturbeerd (Tabel 29).…”
Section: Orgasmefrequentieunclassified
“…성만족도에 대한 지금까지의 선행연구를 보면, 다양한 대상 자에서 성태도 [10][11][12][13], 부부친밀도 [14,15], 성지식 [11], 자아존 중감 [16], 성적 행위 [11], 성의사소통 [ 연 구 결 과 …”
unclassified